CHARACTER EDUCATION VALUES IN THE NOVEL "LEBIH SENYAP DARI BISIKAN" BY ANDINA DWIFATMA BASED ON SOCIOLOGICAL LITERARY STUDY - Nila Sudarti; Nita Nurzanah; Dra. Tuti Herawati (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The objective of this investigation is to determine the educational character value found in Andina Dwifatma’s novel, "Lebih Senyap dari Bisikan". The object of this research is the novel Lebih Senyap dari Bisikan by Andina Dwifatma. The method in this study is descriptive qualitative which analyzes the value of educational character in the study of sociology of literature. The data in this study are the sentences in the text of the novel Lebih Senyap dari Bisikan by Andina Dwifatma. Techniques for taking notes and reading are used to analyze data. The study’s findings demonstrate that the religious education principles of family values, prayer, sincerity, cooperation, thankfulness, and learning to recite the Quran are among the character education values found in Andina Dwifatma’s novel Lebih Senyap dari Bisikan. The values of nationalist education include the values of discipline, protecting the environment, love of the motherland, achievement, and appreciation of the nation’s culture. The importance of self-education encompasses the values of bravery, professionalism, and hard effort. The importance of empathy and mutual assistance is part of the education that comes with mutual cooperation. Honesty and accountability are two virtues that education imparts.